Bajapuik Tradition From The Perspective Of Maslahah Mursalah Wahbah Zuhaili And Symbolic Interactionism Theory - Silvia, Nada; Yasin, Noer; Toriquddin, Moh. (Prodi Sosiologi Agama, 2024)
This study explains the bajapuik tradition, which is a tradition that indicates that there is an invitation money that must be given to the male side by the woman carried out during the custom before marriage, namely the suitor, the bajapuik tradition only occurs in Pariaman and is not found in other Minangkabau canagarian canagarian According to the community, this tradition is different from what Islamic law dictates that men should ask for and prepare money, this tradition will be seen from the perspective of Wahbah Zuhaili's mursalah maslahah and the theory of Symbolic Interactionism to establish laws and reveal the meaning and effect of the tradition. This research method uses ethnography and interviews. The results showed that there is no nash that prohibits women from asking for men by giving a certain amount of money, this tradition is also in line with the mursalah maslahah Wahbah Zuhaili who demands that a matter must contain public benefit values not only personal, this tradition also has the meaning of mutual respect for the families of both parties but arises as a result of the symbol, namely: Fueling the fact that there is competition among male families for higher amounts of pickup money. Then came the traditional terms